Complex analysis and mathematical modeling of the internal exposure dose of the Ukrainian Polissya rural population - H. Chobotko; L. Raichuk; A. Cherniavskyi; N. Liubashenko; I. McDonald (Ядерна фізика та енергетика)
The aim of this research is to determine the socio-economic and environmental factors that influence the formation of the internal exposure dose of the rural population of the radioactively contaminated territory of the Ukrainian Polissya. The most important ecological and socio-economic factors influencing the internal exposure dose were established and applied to the Group Average clustering algorithm and the principal component analysis. Based on the analysis results, the authors developed a mathematical model and created the appropriate software to form a proper assessment of the internal exposure dose in the human body many years after the Chornobyl accident.